Acute Concurrent Exercise Improves Inhibitory Control Without Mediating the Role of Lactate: An Event-Related Potential Study - Ruei-Hong Li; Tai-Rui Chen; Nicholas D. Gilson; Marius Brazaitis; Yi-Ting Cheng; Hui-Fang Wu; Ji-Hang Lee; Yu-Kai Chang (Sports Medicine - Open)
Abstract Background Concurrent exercise (CE), an emerging exercise modality characterized by sequential bouts of aerobic (AE) and resistance exercise (RE), has demonstrated acute benefits on executive functions (EFs) and neuroelectric P3 amplitude. However, the effect of acute CE on inhibitory control, a sub-component of EFs, and P3 amplitude remains inconclusive. Moreover, exploring the mechanisms underlying the effects of acute exercise on EFs contributes to scientific comprehension, with lactate recognized as a crucial candidate positively correlated with EFs. Therefore, this study aimed to determine the effects of acute CE on inhibitory control via behavioral and event-related potential approaches and to examine its potential mediational role on lactate. Methods Seventy-eight adults (mean age = 22.95, SD = 1.75 years) were randomly assigned to either a CE, AE, or control (CON) group. Participants in the CE group engaged in 12-min of AE (40–59% of heart rate reserve [HRR]) coupled with 13-min of RE (1 set, with 75% of 10-repetition maximum, and 12 repetitions of 8 movements). The AE group participated in 25 min of AE (40–59% HRR). Prior to and following exercise onset, participants in both the CE and AE groups completed a 5-min warm-up and cool-down. Participants in the CON group read books for 35 min. Lactate concentrations were measured at timepoints of 0-, 17-, and 30-min relative to the treatment onset. Response time (RT) and accuracy in the Stroop test, as well as P3 amplitude, were assessed before and after the treatment. Results The results revealed that both the CE and AE groups had significantly shorter RTs compared to the CON group, with no significant differences in accuracy among groups. A decrease in P3 amplitude was observed for the CE group compared to the AE and CON groups. The mediating effects of lactate between acute exercise and inhibitory control were insignificant. Conclusions The findings suggest that both CE and AE improve inhibitory control and CE potentially enhances the efficient allocation of attention resources. The lack of a significant mediating effect of lactate warrants further investigation. Trial registration: ClinicalTrials.gov, NCT06370286. Registered 12 April 2024—Retrospectively registered, https://clinicaltrials.gov/study/NCT06370286 .